PERENCANAAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) PRODUK SERAGAM TINGKAT SLTA PADA UNIT USAHA DUTA COLLECTION SENGONAGUNG PASURUAN - Saisuddin; Nuriyanto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2018)
The Material Requirement Planning (MRP) method is used to control the supply of raw materials in a company. A company to implement policies in raw material planning must have the right calculation so that there are no advantages and disadvantages in the supply of raw materials. This study aims to determine whether the application of the Material Requirement Planning (MRP) method in the